Criminal Law Policy On The Crime Of Desertion Performed By Members Of The Indonesian National Army - Hadi Syahputra, Eko (International Journal of Educational Research & Social Sciences, 2022)
An absolute requirement in military life is to comply with TNI regulations and official orders from each superior in order to uphold a life in the military that is full of high awareness. If these things are violated (desertion), it will only shake the joints of discipline and order in the TNI. The formulation of the problems in this study are: 1) What is the criminal law policy on desertion crimes committed by members of the Indonesian National Armed Forces? 2) What are the obstacles to criminal law policies against desertion crimes committed by members of the Indonesian National Armed Forces and what are the solutions. The author uses a normative juridical approach. The sociological juridical approach emphasizes research that aims to obtain legal knowledge empirically by going directly to the object related to this research. The results of this study are: 1) The criminal law policy against the criminal act of desertion in Indonesian military law is clearly regulated in Article 87 of the Criminal Procedure Code and the punishment for members who become the perpetrators of desertion is regulated in Article 88 of the Criminal Procedure Code. The application of military law against the perpetrators of the crime of desertion as a Military Member (TNI) carries a heavier penalty than the threat of punishment found in the general public, because the military is not only armed to maintain security but must be disciplined, instead of using desertion. Desertion in this case is absence without permission, intentionally for 30 consecutive days. 2) Obstacles in the implementation of military law against members of the Indonesian National Armed Forces (TNI) who commit the criminal act of desertion in general because the investigations carried out by Military Police investigators still often do not meet the formal and material requirements.